HUBUNGAN PELAKSANAAN PROGRAM MENGURAS, MENUTUP DAN MENDAUR ULANG BARANG BEKAS DENGAN KEJADIAN DBD DI WILAYAH KERJA PUSKESMAS TANDENGAN KECAMATAN ERIS - Laotji, Novianty Gabriella; Toar, Jilly; Bawiling, Nancy (JURNAL ILMIAH KESEHATAN MANADO, 2024)
Background: Dengue Hemorrhagic Fever (DHF) is an infection caused by the dengue virus which can attack all ages, from babies to the elderly. The way to eradicate mosquito nests is by implementing a program for draining, covering and recycling used goods or commonly known as the 3M program. Objective: To determine the relationship between the implementation of the waste, closing and recycling program for used goods and the incidence of dengue fever in the Tandengan Community Health Center working area, Eris District. Methodology: The research uses a quantitative cross sectional study design method which was carried out in May 2024. Sampling used total sampling or the entire population with a total of 30 samples. The research was carried out by observing the implementation variables of the 3M and DBD programs. The analysis carried out was univariate and bivariate (Chi-Square test). Results: The independent variables that have a significant relationship with the incidence of dengue fever are the implementation of the landfill draining program (p = 0.000 < 0.05), the implementation of the landfill closing program (p = 0.005 < 0.05) and the implementation of the used goods recycling program (p = 0.001 > 0.05). Conclusion: There is a relationship between the implementation of the program for draining, closing and recycling used goods and the incidence of dengue fever in the Tandengan Community Health Center working area, Eris District.